PENGARUH KOMITMEN ORGANISA SI DAN ETOS KERJA TERHADAP PELAYANAN PUBLIK PEGAWAI DINAS SOSIAL TENAGA KERJA DAN TRANSMIGRASI KABUPATEN BREBES - Amsirun amsirun (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2016)
ABSTRACT This study entitled The Effect of Organizational Commitment and Organizational Culture on Employee Satisfaction in the Regional General Hospital of Brebes Regency. The objectives to be achieved in this study are: 1. To find out the significant effect of organizational commitment and organizational culture on employee satisfaction in the Brebes District General Hospital. 2. To find out the factors that most influence the satisfaction of employees of the Regional General Hospital of Brebes Regency. While the hypothesis proposed is: 1. It is assumed that there is a significant influence of organizational commitment and organizational culture on employee satisfaction in the Regional General Hospital of Brebes Regency. 2. It is assumed that organizational culture factors that influence the satisfaction of employees of the Regional General Hospital of Brebes Regency .. The research method used is a case study of the Brebes District General Hospital, while the data collection methods used were surveys, interviews, questionnaires and library research. In testing the hypothesis used the multiple regression coefficient analysis tool with the normality test, t and F. The results of the analysis can be concluded: 1. From the results of linear regression calculation, the multiple linear regression equation didapat = -2,000 + 0,266 X1 + 0,779 X2 is obtained. Based on the results of calculations, at a confidence level of 95% (α = 0.05) and degrees of freedom (2) (77), then obtained F count of 30,259 while F table at the level of trust and the same degree of freedom is 3.47. Thus Fcount> Ftable, then the null hypothesis is rejected, meaning that the influence of organizational commitment and organizational culture variables together on employee performance is significant (meaning) or in other words there is a significant effect of variable organizational commitment and organizational culture together - equal to employee satisfaction. 2. From the partial regression calculation obtained organizational commitment (X1) of 0.457, meaning that the level of organizational commitment (X1) contributes to the 14 improvement of employee satisfaction in the Regional General Hospital of Brebes Regency by 0.457 or 45.70%, this is assuming if the other variables such as organizational culture (X2) is fixed, whereas organizational culture (X2) is 0.811, meaning that the level of organizational culture (X2) contributes to the increase in employee satisfaction of the Brebes Regency Regional General Hospital by 0.811 or 81.10%, assuming if other variables such as organizational commitment (X1) are fixed, thus organizational culture is the most influential factor on employee satisfaction at Brebes District Hospital. Suggestions: 1. From the results of the research conducted, the most dominant variable in influencing employee satisfaction is organizational commitment. With a good organizational commitment can affect employee satisfaction in order to improve organizational performance. Good organizational commitment can make employees feel comfortable at work and employees feel more responsible so that employees can maximize their ability to work better and pay attention to the level of accuracy in work to improve public service performance. 2. To be able to increase employee satisfaction there is a need for an attitude that values high on hard work and earnest. If you need to find an appropriate impulse to motivate and change attitudes. For this reason, it is necessary to instill organizational goals in the vision, mission, philosophy and organization motto is an ideal value that must be achieved in individuals. With the right process organizations try to instill value in their members. The ideal value perceived by its members will influence the assessment of itself. These values are instilled by the organization with the main goal of increasing performance and quality of work. Good work performance and quality can be achieved with a good work culture.